Effects of Si doping well beyond the Mott transition limit in GaN epilayers grown by plasma-assisted molecular beam epitaxy - Lingaparthi, R. (2022)
The effects of Si doping well beyond the Mott transition limit on the structural, electrical, and optical properties of plasma assisted molecular beam epitaxy grown GaN layers were studied. Si doping up to a doping density of <1.0 × 1020 cm-3 resulted in smooth surface morphologies and almost strain free 500 nm thick GaN layers on 50 mm Si (111) substrate. In this doping range, the crystal quality improved with increased Si doping. However, GaN layers with doping density of >1.0 × 1020 cm-3 resulted in rough surface morphology and degraded crystal quality. It also showed higher tensile strain, but did not result in cracking. Irrespective of the surface morphology and structural quality, the sheet resistance systematically decreased with increased carrier concentration up to and beyond the doping density of 1.0 × 1020 cm-3. PL study revealed three distinctive characteristics with Si doping: first, yellow luminescence is absent in Si doped samples - an indication of occupied VGa-ON and CN states in the bandgap; second, a distinctive luminescence peak is observed next to the band edge luminescence (BEL) for the samples doped beyond 2.1 × 1019 cm-3 - probably an indication of localization of some of the electrons either at donors or at excitons bound to defects; third, blue shift of the BEL is not matching with the calculated Moss-Burstein shift for doping densities beyond 2.1 × 1019 cm-3 - an indication of some of the electrons not occupying higher levels of conduction band, which is consistent with the second observation of localization of electrons near the donors or excitons bound to surface defects.